INTEGRATION OF KNOWLEDGE: Comparison of Experiences in Malaysian and Indonesian Universities - Doll Kawaid, A. Irwan Santeri; Yabi, Shumsudin; Syed Hassan, Syed Najihuddin; Mujab, M.; Kahar, Syadidul (State Islamic University North Sumatra, 2025)
Efforts to integrate science and revelation in Islamic campuses have been underway since the 1970s; however, the extent to which these aspirations have been achieved still requires further discussion. This study examines how the integration of knowledge is manifested at USIM and UIN SU Medan. The focus is on the theoretical-philosophical framework, objectives, implementation processes, strategic priorities, and challenges of science integration. The research primarily relies on written data from guidebooks and reports on science integration at both campuses, analyzed using Content Analysis. The study found that both campuses share similarities in terms of philosophy and theory of integration, despite using different terminologies and jargons. They also face relatively similar challenges. On the other hand, there are significant differences between the two campuses in terms of governance and clarity of work plans. As an experience, the findings of this study can contribute to similar efforts at other campuses.